PENGARUH ALAT PERAGA BERBASIS AUGMENTED REALITY TERHADAP HASIL BELAJAR MATEMATIKA SISWA SEKOLAH DASAR - Siti Dinarti (Program Studi Pendidikan Matematika STKIP PGRI Sidoarjo, 2024)
This study aims to examine the effect of using augmented reality (AR) based teaching aids on elementary school students' math learning outcomes. Augmented reality technology offers an innovative solution by providing a clearer and more real visualization of mathematical concepts, as well as creating a more interactive and interesting learning experience. The design used in this research is pre-experimental design. The design type used in this research is one group pretest-posttest. This research was conducted at SDN Palrejo 1 Sumobito Jombang with the population used in this study were all fourth grade students totaling 33 students. The sample used was the entire population (saturated sampling). Data collection techniques using tests, namely pretest and posttest and data analyzed using the SPSS application. Data analysis using paired simple t test. The results of the data analysis that have been analyzed, namely it is known that the value of Sig. (2- tailed) of 0.000>0.05, it can be concluded that there is a difference in student learning outcomes between before and after being given treatment using augmented reality-based teaching aids. The results showed that the use of AR-based teaching aids significantly improved students' math learning outcomes. In addition, students' acceptance of the use of AR technology in learning mathematics is also very positive. The conclusion of this study is that the use of augmented reality-based teaching aids can be an effective learning method in improving elementary school students' mathematics learning outcomes.